Modified iron-based biochar composite material, preparation method and application thereof in rapid recovery of seriously acidified kitchen waste anaerobic project

CN119218994BActive Publication Date: 2026-10-30北京时代桃源环境科技股份有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411439775.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2026-10-30
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

[0004]鉴于以上所述现有技术的缺点,本发明的目的在于提供一种改性铁基生物炭复合材料,用于解决现有技术中无法在不停产的情况下实现对严重酸化厌氧体系的快速恢复的问题,同时,本发明还将提供改性铁基生物炭复合材料的制备方法;此外,本发明还将提供改性铁基生物炭复合材料在快速恢复严重酸化餐厨垃圾厌氧工程中的应用

Benefits of technology

本发明在制备改性铁基生物炭复合材料的过程中,通过活化处理使生物炭具有更高的比表面积和多孔结构,提高其吸附能力,并且能够掺杂更多的铁元素,促进电子传递,强化产酸菌与产甲烷菌之间的电子传递过程;另外,通过在铁基生物炭的表面包覆导电聚合物,可以明显提高材料整体的导电性和电子传递效率,完善产酸菌和产甲烷菌之间的电子传递网络,极大的提高了厌氧消化效率,从而能够快速恢复严重酸化餐厨垃圾厌氧体系。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119218994B_ABST
    Figure CN119218994B_ABST
Patent Text Reader

Abstract

The application provides a modified iron-based biochar composite material, a preparation method and application of the modified iron-based biochar composite material in rapid recovery of an anaerobic engineering of seriously acidified kitchen waste, and the preparation method comprises the steps of low-temperature carbonization treatment, activation treatment, modification by a coprecipitation method, surface coating of a conductive polymer and the like. In the process of preparing the modified iron-based biochar composite material, the biochar has a higher specific surface area and porous structure through the activation treatment, the adsorption capacity is improved, more iron elements can be doped, the electron transfer is promoted, and the electron transfer process between acid-producing bacteria and methanogenic bacteria is strengthened; in addition, the conductivity and electron transfer efficiency of the whole material can be obviously improved through the surface coating of the conductive polymer on the iron-based biochar, the electron transfer network between the acid-producing bacteria and the methanogenic bacteria is perfected, the anaerobic digestion efficiency is greatly improved, and therefore the anaerobic system of the seriously acidified kitchen waste can be rapidly recovered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of anaerobic digestion technology, and in particular to a modified iron-based biochar composite material, its preparation method, and its application in the rapid recovery of severely acidified kitchen waste through anaerobic digestion. Background Technology

[0002] Anaerobic digestion is one of the best technological approaches to reduce environmental pollution from biomass waste and recover its inherent clean energy. Organic solid waste, such as organic waste, has a high organic content and high moisture content. Anaerobic digestion of organic waste offers advantages such as low energy consumption, small footprint, and reduced secondary pollution. However, food waste is highly susceptible to acidification during anaerobic digestion. High salt content, excessively rapid acidification during hydrolysis, high levels of pathogens, low C / N ratio, high alkalinity during fermentation, limited range of functional microbial species, nutrient imbalance, overload operation, severe deviations in pH and temperature control, and the influx of toxic substances are all contributing factors to the anaerobic acidification of food waste.

[0003] Currently, the main method to restore an acidified anaerobic system is to stop feeding, clean the tank, and re-inoculate and cultivate the waste. However, this process is very slow, often taking three to four months or more to restore normal daily feeding as before acidification. Furthermore, the disposal of acidified materials also presents environmental challenges. This results in significant losses for existing food waste treatment projects and has a severe negative social impact. Therefore, there is an urgent need for a rapid, uninterrupted recovery method for severely acidified food waste treatment projects. Summary of the Invention

[0004] In view of the shortcomings of the prior art described above, the purpose of this invention is to provide a modified iron-based biochar composite material to solve the problem that the prior art cannot achieve rapid recovery of severely acidified anaerobic systems without interrupting production. Furthermore, this invention will also provide a method for preparing the modified iron-based biochar composite material; in addition, this invention will also provide the application of the modified iron-based biochar composite material in the rapid recovery of severely acidified kitchen waste anaerobic processes.

[0005] To achieve the above and other related objectives, the present invention provides the following technical solutions: In a first aspect, the present invention provides a method for preparing a modified iron-based biochar composite material, comprising the following steps: S1. Using biomass rich in lignocellulose as raw material, the crushed raw material is subjected to low-temperature carbonization in an oxygen-deficient environment to obtain pre-oxidized biochar. S2. The pre-oxidized biochar is activated to obtain activated biochar. S3. Iron-based materials are modified onto the surface of activated biochar by co-precipitation to obtain iron-based biochar; S4. Dissolve the conductive polymer monomer in a solvent, uniformly disperse the iron-based biochar in the conductive polymer monomer solution, heat the mixed solution to carry out an in-situ polymerization reaction, thereby coating the surface of the iron-based biochar with conductive polymer. S5. After the reaction is complete, the product is separated, washed, and dried to obtain the modified iron-based biochar composite material.

[0006] The preferred solution for step S1 is as follows: The lignocellulose-rich biomass is selected from at least one of sawdust, bamboo, fruit shells, rice husks, and coconut shells. These biomass raw materials contain abundant organic components, easily form porous structures, and are widely available and inexpensive.

[0007] The particle size of the pulverized raw material is between 80 mesh and 120 mesh. Preferably, the particle size of the pulverized raw material is 100 mesh.

[0008] The temperature for low-temperature carbonization is between 300 and 500°C, and the carbonization time is between 0.5 and 1 hour.

[0009] The preferred solution for step S2 is as follows: The activation process includes: mixing pre-oxidized biochar with an activator solution, heating and reacting for a period of time, and then separating, washing, and drying the biochar after the reaction is complete to obtain activated biochar.

[0010] The activator is selected from phosphoric acid or sulfuric acid. After activation, the porosity and specific surface area of ​​biochar can be increased, which not only enhances the biochar's ability to adsorb VFA, but also ensures that iron ions are fully loaded onto the surface and pores of the biochar, improves the conductive network of iron ions, and achieves more efficient electron transfer.

[0011] The activation temperature is between 400 and 600℃, and the activation time is between 1 and 2 hours.

[0012] The preferred solution for step S3 is as follows: The iron-based materials include ferric chloride (FeCl3) and ferrous sulfate (FeSO4).

[0013] The coprecipitation modification process includes: dissolving FeCl3·6H2O and FeSO4·7H2O in water to prepare a mixed iron salt solution; fully immersing the activated biochar in the iron salt solution; raising the temperature and adjusting the pH during stirring to induce a coprecipitation reaction of the iron salts; and separating, washing, and drying the iron-based biochar after the reaction is complete.

[0014] The temperature of the coprecipitation reaction is between 60 and 80°C, and the pH of the coprecipitation reaction is between 8.5 and 10.

[0015] The molar ratio of FeCl3 to FeSO4 is between 2:1 and 1:2; preferably (1 to 1.5):1.

[0016] During the coprecipitation reaction, iron oxide precipitates form on the surface of biochar, which can enhance its catalytic, adsorption and electrical conductivity functions. Moreover, the coprecipitation method has simple operation steps and is suitable for industrial production.

[0017] The preferred solution for step S4 is as follows: The conductive polymer is selected from at least one of polyaniline, polypyrrole, polythiophene, and polyethylene dioxythiophene. Correspondingly, the conductive polymer monomer is selected from at least one of aniline, pyrrole, thiophene, and polyethylene dioxythiophene.

[0018] The solvent is selected from water, alcohols, ketones, or ethers.

[0019] An oxidant is also added during the in-situ polymerization reaction, and the oxidant includes at least one selected from persulfate and chlorate. Preferably, the oxidant is selected from at least one selected from ammonium persulfate, sodium persulfate, sodium chlorate, and potassium chlorate. More preferably, the amount of persulfate added is equivalent to 0.5-5% of the amount of conductive polymer monomer added, and the amount of chlorate added is equivalent to 0.1-1% of the amount of conductive polymer monomer added.

[0020] The in-situ polymerization reaction is carried out at a temperature between 60 and 120°C, and the reaction time is between 12 and 36 hours.

[0021] An acidic solution needs to be added to the mixed solution to adjust the pH to acidic; preferably, the pH is adjusted to 3-5.

[0022] The modified iron-based biochar composite material prepared by this invention not only has a high specific surface area and porous structure, which can effectively adsorb VFA and thus reduce the concentration of VFA in the tank; but also can achieve electron transfer through the redox reaction of iron ions, which can independently participate in the biomethanation process of organic matter and accelerate the conversion of VFA; in addition, by coating the surface of the iron-based biochar with conductive polymer, the overall conductivity and electron transfer efficiency can be significantly improved, serving as a more efficient electron transfer mode.

[0023] In a second aspect, the present invention provides a modified iron-based biochar composite material, wherein the modified iron-based biochar composite material is prepared by the above-described preparation method.

[0024] A third aspect of the present invention provides a method for applying a modified iron-based biochar composite material in a rapid recovery anaerobic process for severely acidified kitchen waste.

[0025] In this process, the modified iron-based biochar composite material is added to a severely acidified anaerobic tank, with the amount of the modified iron-based biochar composite material being added being 0.5% to 0.1% of the total amount in the tank.

[0026] The application method specifically includes the following steps: (1) Modified iron-based biochar composite material is added to the severely acidified anaerobic tank using a dosing device. The initial start-up amount of the modified iron-based biochar composite material is added at 0.5% of the amount of slurry in the tank. (2) Resume feeding when the organic load drops from 0 kg VS / m 3 Up to 0.5kg VS / m 3 During this phase, the daily feed rate increases by 15% compared to the previous day, and the daily dosage of modified iron-based biochar composite material is calculated as feed rate (t / d) * TS content (%) * 5%. (3) When the organic load is reduced from 0.5 kg VS / m 3 Up to 1.0 kg VS / m 3 During this phase, the daily feed rate increases by 10% compared to the previous day, and the daily dosage of modified iron-based biochar composite material is feed rate (t / d) * TS content (%) * 4%; (4) When the organic loading rate is 1.0 kg VS / m 3 Up to 2.0kg VS / m 3 During this phase, the daily feed rate increases by 5% compared to the previous day, and the daily dosage of modified iron-based biochar composite material is feed rate (t / d) * TS content (%) * 3%; (5) When the organic load changes from 2.0 kg VS / m 3 Up to 3.0kg VS / m 3 During this phase, the daily feed rate increases by 3% compared to the previous day, and the daily dosage of modified iron-based biochar composite material is feed rate (t / d) * TS content (%) * 2%; (6) When the organic load reaches 3.0 kg VS / m 3 Normal daily feed is maintained, but the addition of modified iron-based biochar composite material is stopped.

[0027] The daily feed parameters include: feed volume, total suspended solids (TS), volatile solids (VS), and pH.

[0028] In step (2), after the feed is resumed, the feed rate increases from 1t / d.

[0029] Furthermore, the process of step (2) lasts for 7 days, the process of step (3) lasts from the 8th day to the 15th day, the process of step (4) lasts from the 16th day to the 29th day, and the process of step (5) lasts from the 30th day to the 42nd day.

[0030] During application, production can be started directly after adding iron-based biochar without stopping production. With the help of modified iron-based biochar composite materials, the daily feed load can be increased rapidly, and production can be achieved sooner; moreover, it can recover from a severely acidified state to full production within 45 days, which shortens the construction period by 45 days or more compared to the traditional method of cleaning the tank first and then inoculating and cultivating.

[0031] Because this modified iron-based biochar composite material is used to rescue acidified anaerobic digesters, there is no need for tank cleaning, eliminating the problem of acidified liquid disposal and avoiding environmental issues and high disposal costs. The use of this modified iron-based biochar composite material to rescue acidified anaerobic digesters is not simply a physicochemical process, but rather the construction of a stable microbial system. The pH, VFA, TAC (total alkalinity), TS, VS, COD (chemical oxygen demand), ammonia nitrogen, and biogas composition within the anaerobic digester remain stable. During the acidification recovery period and for a period afterward, the methane content in the biogas is significantly higher than the pre-acidification value, which is beneficial for improving the economic value of the biogas.

[0032] Furthermore, the anaerobic tank is equipped with a stirrer, which can make the temperature inside the tank uniform, and the temperature fluctuation inside the anaerobic tank does not exceed 1°C.

[0033] Furthermore, the anaerobic digester is equipped with a level gauge, temperature sensor, pressure sensor, biogas flow meter, gas analyzer, and pH meter. These instruments enable real-time monitoring of pH, VFA, TAC (total alkalinity), TS, VS, COD (chemical oxygen demand), ammonia nitrogen, and biogas composition within the anaerobic digester, ensuring their stability and providing an additional layer of assurance for determining whether the acidification system has returned to normal.

[0034] As described above, the modified iron-based biochar composite material, its preparation method, and its application in the rapid recovery of severely acidified kitchen waste anaerobic digestion have the following beneficial effects: In the preparation of modified iron-based biochar composite materials, this invention utilizes activation treatment to give the biochar a higher specific surface area and porous structure, thereby improving its adsorption capacity. Furthermore, it allows for the incorporation of more iron, promoting electron transfer and enhancing the electron transfer process between acid-producing and methanogenic bacteria. Additionally, by coating the surface of the iron-based biochar with a conductive polymer, the overall conductivity and electron transfer efficiency of the material are significantly improved, perfecting the electron transfer network between acid-producing and methanogenic bacteria, and greatly enhancing anaerobic digestion efficiency. This enables the rapid restoration of severely acidified food waste anaerobic systems. Attached Figure Description

[0035] Figure 1 The diagram shown is a structural schematic of the anaerobic digester disclosed in this invention.

[0036] Attached reference numerals: 1. Anaerobic tank; 2. Level gauge; 3. Temperature sensor; 4. Agitator; 5. Pressure sensor; 6. Biogas flow meter; 7. Biogas analyzer; 8. Dosing device; 9. pH meter. Detailed Implementation

[0037] The following specific embodiments illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification.

[0038] Example 1 A modified iron-based biochar composite material is obtained by the following preparation method: S1. The wood chips from the wood processing plant are crushed and passed through a 100-mesh sieve, and then carbonized at a low temperature of 400℃ for 1 hour in an oxygen-deficient environment to obtain pre-oxidized biochar. S2. The pre-oxidized biochar is added to a 30% phosphoric acid solution and activated at 500℃ for 1 hour to obtain activated biochar. S3. FeCl3·6H2O and FeSO4·7H2O were dissolved in water to prepare iron salt solutions with concentrations of 0.08M and 0.1M, respectively. The solutions were mixed, and the activated biochar was fully immersed in the mixed iron salt solution. During stirring, the temperature was raised to 70℃ and sodium hydroxide was added to adjust the pH to 9 to induce a co-precipitation reaction of the iron salts. The reaction was carried out for 2 hours. After the reaction was completed, the biochar was separated, washed, and dried to obtain iron-based biochar. S4. Dissolve 200 μL of pyrrole in 500 mL of water, take 15 g of the iron-based biochar prepared above and disperse it evenly in the pyrrole solution, add hydrochloric acid to adjust the pH to 5, add 50 μL of 10% ammonium persulfate solution, mix evenly, and then heat the mixed solution to 80℃ to carry out in-situ polymerization reaction for 12 h, thereby coating the surface of the iron-based biochar with polypyrrole. S5. After the reaction is complete, the product is separated by centrifugation, washed sequentially with deionized water and anhydrous ethanol, and dried in an oven at 80°C for 24 hours to obtain the modified iron-based biochar composite material.

[0039] Example 2 A modified iron-based biochar composite material is obtained by the following preparation method: S1. The wood chips from the wood processing plant are crushed and passed through a 100-mesh sieve, and then carbonized at a low temperature of 400℃ for 1 hour in an oxygen-deficient environment to obtain pre-oxidized biochar. S2. The pre-oxidized biochar is added to a 30% phosphoric acid solution and activated at 500℃ for 1 hour to obtain activated biochar. S3. FeCl3·6H2O and FeSO4·7H2O were dissolved in water to prepare iron salt solutions with concentrations of 0.08M and 0.1M, respectively. The solutions were mixed, and the activated biochar was fully immersed in the mixed iron salt solution. During stirring, the temperature was raised to 70℃ and sodium hydroxide was added to adjust the pH to 9 to induce a co-precipitation reaction of the iron salts. The reaction was carried out for 2 hours. After the reaction was completed, the biochar was separated, washed, and dried to obtain iron-based biochar. S4. Dissolve 200 μL of aniline in 500 mL of water, take 15 g of the iron-based biochar prepared above and disperse it evenly in the aniline solution, add hydrochloric acid to adjust the pH to 3, add 10 μL of 10% ammonium persulfate solution, mix evenly, then heat the mixed solution to 80℃ and perform in-situ polymerization reaction for 12 h, thereby coating the surface of the iron-based biochar with polyaniline. S5. After the reaction is complete, the product is separated by centrifugation, washed sequentially with deionized water and anhydrous ethanol, and dried in an oven at 80°C for 24 hours to obtain the modified iron-based biochar composite material.

[0040] Example 3 A modified iron-based biochar composite material is obtained by the following preparation method: S1. Crush the coconut shells and pass them through a 100-mesh sieve. Then, carbonize them at a low temperature of 400℃ for 1 hour in an oxygen-deficient environment to obtain pre-oxidized biochar. S2. The pre-oxidized biochar is added to a 30% phosphoric acid solution and activated at 500℃ for 1 hour to obtain activated biochar. S3. FeCl3·6H2O and FeSO4·7H2O were dissolved in water to prepare iron salt solutions with concentrations of 0.1M and 0.1M, respectively. The solutions were mixed, and the activated biochar was fully immersed in the mixed iron salt solution. During stirring, the temperature was raised to 70℃ and sodium hydroxide was added to adjust the pH to 9 to induce a co-precipitation reaction of the iron salts. The reaction was carried out for 2 hours. After the reaction was completed, the biochar was separated, washed, and dried to obtain iron-based biochar. S4. Dissolve 200 μL of thiophene in 500 mL of water and add 0.001 g of sodium chlorate. Mix well. Take 15 g of the iron-based biochar prepared above and disperse it evenly in the pyrrole solution. Add hydrochloric acid to adjust the pH to 3. Then heat the mixed solution to 100 °C and perform in-situ polymerization for 12 h to coat the surface of the iron-based biochar with polythiophene. S5. After the reaction is complete, the product is separated by centrifugation, washed with deionized water and anhydrous ethanol in sequence, and dried in an oven at 60°C for 24 hours to obtain the modified iron-based biochar composite material.

[0041] Example 4 A modified iron-based biochar composite material is obtained by the following preparation method: S1. Crush the bamboo and pass it through a 100-mesh sieve. Then, carbonize it at a low temperature of 400℃ for 1 hour in an oxygen-deficient environment to obtain pre-oxidized biochar. S2. The pre-oxidized biochar is added to a 30% phosphoric acid solution and activated at 500℃ for 1 hour to obtain activated biochar. S3. FeCl3·6H2O and FeSO4·7H2O were dissolved in water to prepare iron salt solutions with concentrations of 0.08M and 0.1M, respectively. The solutions were mixed, and the activated biochar was fully immersed in the mixed iron salt solution. During stirring, the temperature was raised to 70℃ and sodium hydroxide was added to adjust the pH to 9 to induce a co-precipitation reaction of the iron salts. The reaction was carried out for 2 hours. After the reaction was completed, the biochar was separated, washed, and dried to obtain iron-based biochar. S4. Dissolve 300 μL of ethylene dioxythiophene (EDOT) in 500 mL of water. Take 15 g of the iron-based biochar prepared above and disperse it evenly in the aniline solution. Add hydrochloric acid to adjust the pH to 5, and add 20 μL of 10% ammonium persulfate solution. Mix well, and then heat the mixed solution to 80 °C and perform in-situ polymerization for 24 h to coat the surface of the iron-based biochar with polyaniline. S5. After the reaction is complete, the product is separated by centrifugation, washed sequentially with deionized water and anhydrous ethanol, and dried in an oven at 80°C for 24 hours to obtain the modified iron-based biochar composite material.

[0042] Comparative Example 1 An iron-based biochar is obtained by the following preparation method: S1. The wood chips from the wood processing plant are crushed and passed through a 100-mesh sieve, and then carbonized at a low temperature of 400℃ for 1 hour in an oxygen-deficient environment to obtain pre-oxidized biochar. S2. The pre-oxidized biochar is added to a 30% phosphoric acid solution and activated at 500℃ for 1 hour to obtain activated biochar. S3. FeCl3·6H2O and FeSO4·7H2O were dissolved in water to prepare iron salt solutions with concentrations of 0.08M and 0.1M, respectively. The two solutions were mixed, and the activated biochar was fully immersed in the mixed iron salt solution. During stirring, the temperature was raised to 70℃ and sodium hydroxide was added to adjust the pH to 9 to induce a co-precipitation reaction of the iron salts. The reaction was carried out for 2 hours. After the reaction was completed, the biochar was separated, washed, and dried to obtain iron-based biochar.

[0043] Comparative Example 2 An iron-based biochar is obtained by the following preparation method: S1. The wood chips from the wood processing plant are crushed and passed through a 100-mesh sieve, and then carbonized at a low temperature of 400℃ for 1 hour in an oxygen-deficient environment to obtain biochar. S2. FeCl3·6H2O and FeSO4·7H2O were dissolved in water to prepare iron salt solutions with concentrations of 0.08M and 0.1M, respectively. The two solutions were mixed, and the biochar was fully immersed in the mixed iron salt solution. During stirring, the temperature was raised to 70℃ and sodium hydroxide was added to adjust the pH to 9 to induce a co-precipitation reaction of the iron salts. The reaction was carried out for 2 hours. After the reaction was completed, the biochar was separated, washed, and dried to obtain iron-based biochar.

[0044] Test Kitchen waste (organic biodegradable matter 61.5±3%, paper products 16.8±1%, fruit peels 13.4±1%, plastics 8.3±1%, pH 6.7~7.3, solids content 20±2%, volatile solids 16±2%) was crushed and homogenized. Inoculated sludge was mixed with kitchen waste at a mass ratio of 2:1. The mixture was added to an anaerobic digester equipped with a stirrer, a level gauge, a temperature sensor, a pressure sensor, a biogas flow meter, a gas analyzer, and a pH meter. Water was added to dilute the mixture to a solids content of 10%, the temperature was set to 35℃, and the stirrer speed was set to 35 rpm. Additives (or none) were added at a rate of 0.5% of the slurry volume. No further feeding or discharging occurred during the experiment, which lasted for 20 days. Methane production rate and conductivity were measured. Table 1 shows the effect of different materials on the methane production efficiency of kitchen waste.

[0045] In summary, this invention, in the preparation of modified iron-based biochar composite materials, utilizes activation treatment to give the biochar a higher specific surface area and porous structure, enhancing its adsorption capacity. Furthermore, it allows for the incorporation of more iron, promoting electron transfer and strengthening the electron transfer process between acid-producing and methanogenic bacteria. Additionally, coating the surface of the iron-based biochar with a conductive polymer significantly improves the overall conductivity and electron transfer efficiency of the material, perfecting the electron transfer network between acid-producing and methanogenic bacteria, and greatly improving anaerobic digestion efficiency. This enables the rapid restoration of severely acidified food waste anaerobic systems. Therefore, this invention effectively overcomes the various shortcomings of existing technologies and possesses high industrial application value.

[0046] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the invention. Any person skilled in the art can modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by those skilled in the art without departing from the spirit and technical concept disclosed in the present invention should still be covered by the claims of the present invention.

Claims

1. A method for rapidly restoring severely acidified kitchen waste anaerobic digestion using modified iron-based biochar composite materials, characterized in that, Includes the following steps: (1) Modified iron-based biochar composite material is added to the severely acidified anaerobic tank using a dosing device. The initial start-up amount of the modified iron-based biochar composite material is added at 0.5% of the amount of slurry in the tank. (2) Resume feeding when the organic load drops from 0 kg VS / m 3 Up to 0.5kg VS / m 3 During this phase, the daily feed rate increases by 15% compared to the previous day, and the daily dosage of modified iron-based biochar composite material is equal to the feed rate. TS content 5%, the unit of feed rate is t / d; (3) When the organic load is reduced from 0.5 kg VS / m 3 Up to 1.0 kg VS / m 3 During this phase, the daily feed rate increases by 10% compared to the previous day, and the daily dosage of modified iron-based biochar composite material is equal to the feed rate. TS content 4%, the unit of feed rate is t / d; (4) When the organic loading rate is 1.0 kg VS / m 3 Up to 2.0kg VS / m 3 During this phase, the daily feed rate increases by 5% compared to the previous day, and the daily dosage of modified iron-based biochar composite material is equal to the feed rate. TS content 3%, the unit of feed rate is t / d; (5) When the organic load changes from 2.0 kg VS / m 3 Up to 3.0kg VS / m 3 During this phase, the daily feed rate increases by 3% compared to the previous day, and the daily dosage of modified iron-based biochar composite material is equal to the feed rate. TS content 2%, the unit of feed rate is t / d; (6) When the organic load reaches 3.0 kg VS / m 3 Normal daily feed, stop adding modified iron-based biochar composite material; The modified iron-based biochar composite material was prepared using the following method: S1. Using biomass rich in lignocellulose as raw material, the crushed raw material is subjected to low-temperature carbonization in an oxygen-deficient environment. The low-temperature carbonization temperature is between 300 and 500℃ to obtain pre-oxidized biochar. S2. Mix the pre-oxidized biochar with the activator solution and heat it to react for a period of time. The activator is selected from phosphoric acid or sulfuric acid. After the reaction is completed, separate, wash and dry to obtain activated biochar. S3. Iron-based materials are modified onto the surface of activated biochar by coprecipitation. The coprecipitation modification process includes: dissolving FeCl3·6H2O and FeSO4·7H2O in water to prepare a mixed iron salt solution; fully immersing the activated biochar in the iron salt solution; raising the temperature and adjusting the pH during stirring to induce a coprecipitation reaction of the iron salts; and separating, washing, and drying the biochar after the reaction to obtain iron-based biochar. S4. Dissolve the conductive polymer monomer in a solvent, uniformly disperse the iron-based biochar in the conductive polymer monomer solution, and heat the mixed solution to initiate an in-situ polymerization reaction, thereby coating the surface of the iron-based biochar with the conductive polymer; the conductive polymer monomer is selected from at least one of aniline, pyrrole, thiophene, and ethylenedioxythiophene, and the conductive polymer is selected from at least one of polyaniline, polypyrrole, polythiophene, and polyethylenedioxythiophene; an oxidant is also added during the in-situ polymerization reaction, and the oxidant includes at least one of persulfate and chlorate; the temperature of the in-situ polymerization reaction is between 60 and 120°C, and the time of the in-situ polymerization reaction is between 12 and 36 hours; S5. After the reaction is complete, the product is separated, washed, and dried to obtain the modified iron-based biochar composite material.

2. The method according to claim 1, characterized in that, In step S1, the low-temperature carbonization time is between 0.5 and 1 hour.

Citation Information

Patent Citations

  • Method for enhancing anaerobic fermentation to produce biogas by using grafted magnetic biochar

    CN116574764A

  • Preparation method of iron-modified straw biogas residue charcoal, and product and application of iron-modified straw biogas residue charcoal

    CN117299756A